Performance Test of Openflow Agent on Openflow Software-Based Mikrotik RB750 Switch - Kartadie, Rikie (Universitas Negeri Semarang, 2016)
A network is usually developed by several devices such as router, switch etc. Every device forwards data package manipulation with complicated protocol planted in its hardware. An operator is responsible for running configuration either to manage rules or application applied in the network. Human error may occur when device configuration run manually by operator. Some famous vendors, one of them is MikroTik, has also been implementing this OpenFlow on its operation. It provides the implementation of SDN/OpenFlow architecture with affordable cost. The second phase research result showed that switch OF software-based MikroTik resulted higher latency value than both mininet and switch OF software-based OpenWRT. The average gap value of switch OF software-based MikroTik is 2012 kbps lower than the value of switch OF software-based OpenWRT. The average gap value of throughput bandwidth protocol UDP switch OF software-based MikroTik is 3.6176 kBps lower than switch OF software-based OpenWRT and it is 8.68 kBps lower than mininet. The average gap throughput jitter protokol UDP of switch OF software-based MiktoTik is 0.0103ms lower than switch OF software-based OpenWRT and 0.0093ms lower than mininet.